POLÍTICAS DE INCLUSÃO APLICADAS NA UNIVERSIDADE FEDERAL DE SANTA CATARINA: GESTÃO SOCIAL OU GESTÃO ESTRATÉGICA? - Kátia Denise Moreira (Revista Gestão Universitária na América Latina, 2011)
The policies of inclusion applied in the Universidade Federal de Santa Catarina (UFSC), are: The Program of Affirmative Actions, which is related with the quota system; The Program Incluir applied to those people that needs special care and the Pré-Vestibular course, which aims to democratize the university access. The objective of this paper is to investigate whether these policies are included in a social management practice or just want to answer the strategic management of the Institution. The methodology is based on the qualitative approach and It is descriptive, based on analysis of documents, books and reports. The result shows that the UFSC inclusion polices are applied from the perspective of strategic management, however there are distinctive elements of social innovation and also there is, in its origins, relation of the social management.